Self-Destructive Behavior Analysis of Hannah Baker in The Thirteen Reasons Why Novel - Jeantriani Febrita; Eka Margianti Sagimin (Jurnal DinamikA, 2020)
This study investigates Self-Destructive Behavior of Hannah Baker in Thirteen Reasons Why novel, conducted in qualitative approach analysis of self-destructive behavior of the main character and what reasons or the causes of it through the narratives in the Thirteen Reasons Why novel. The goal of the study is to analyze how self-destructive behavior impacted the main character, Hannah Baker which is described using the theory of Self-Destructive Behavior and Defense Mechanisms by Sigmund Freud (1966). The result of this study shows that Hannah Baker developed the self-destructive behavior as a defense mechanisms from herself that triggered by trauma from the past. It started with the non-suicidal self-destructive behavior but soon turns into the suicidal self-destructive behavior. This study also shows how a suicide can really be an impact of the behavior that happens in the novel resulted from a non-suicidal self-destructive behavior that is not handled well, and all the mistreatments that the main character felt which produce the desire for ending her life.Keywords: Self-Defense Mechanism, Self-Destructive Behavior, Sigmund Freud, Suicide, Thirteen Reasons Why.